Sum of Squares of Sines

Geometry Level 2

Find the value of sin 2 1 + sin 2 2 sin 2 3 + + sin 2 8 8 sin 2 8 9 + sin 2 9 0 -\sin^2{1^\circ}+\sin^2{2^\circ }-\sin^2{3^\circ }+\ldots+\sin^2{88^\circ}-\sin^2{89^\circ}+\sin^2{90^\circ}

1 2 \frac{1}{2} 0 1 -1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Apr 22, 2015

Let's make use of the fact that sin ( x ) = cos ( 9 0 x ) . \sin(x) = \cos(90^\circ - x). For example, sin ( 1 ) = cos ( 8 9 ) \sin(1^\circ)=\cos(89^\circ) and so on. Thus, we can write

sin 2 1 + sin 2 2 sin 2 3 + . . . + sin 2 8 8 sin 2 8 9 + sin 2 9 0 = sin 2 1 sin 2 8 9 + sin 2 2 + sin 2 8 8 sin 2 3 sin 2 8 7 + . . . . . . sin 2 4 3 sin 2 4 7 + sin 2 4 4 + sin 2 4 6 sin 2 4 5 + sin 2 9 0 = sin 2 1 cos 2 1 + sin 2 2 + cos 2 2 sin 2 3 cos 2 3 + . . . . . . sin 2 4 3 cos 2 4 3 + sin 2 4 4 + cos 2 4 4 sin 2 4 5 + sin 2 9 0 = 1 + 1 1... 1 + 1 ( 1 2 ) 2 + 1 = 22 + 22 1 2 + 1 = 1 2 -\sin^2{1^\circ} + \sin^2{2^\circ}-\sin^2{3^\circ} +...+\sin^2{88^\circ} - \sin^2{89^\circ} +\sin^2{90^\circ} \\ = -\sin^2{1^\circ} - \sin^2{89^\circ} + \sin^2{2^\circ} + \sin^2{88^\circ} - \sin^2{3^\circ} - \sin^2{87^\circ} +... \\ \quad ... -\sin^2{43^\circ} - \sin^2{47^\circ} +\sin^2{44^\circ} + \sin^2{46^\circ} -\sin^2{45^\circ} +\sin^2{90^\circ} \\ = -\sin^2{1^\circ} - \cos^2{1^\circ} + \sin^2{2^\circ} + \cos^2{2^\circ} -\sin^2{3^\circ} - \cos^2{3^\circ} +... \\ \quad ... -\sin^2{43^\circ} - \cos^2{43^\circ} +\sin^2{44^\circ} + \cos^2{44^\circ} -\sin^2{45^\circ} +\sin^2{90^\circ} \\ = -1+1-1...-1+1-\left( \frac{1}{\sqrt{2}} \right)^2 + 1 \\ = -22+22-\frac{1}{2}+1 = \boxed{\frac{1}{2}}

It was really a 30 seconds ques... :D

Rishabh Tripathi - 5 years, 11 months ago

Please describe the solution completely to me I'm not so good in trigonometry

SHOAIB ur REHMAN - 6 years, 1 month ago

Log in to reply

Well basically to solve this type of problems you need to know a couple things. 1.How to change sin to cos, csc to sec and tan to cot. 2.Some common trig identities.

For this one; note that, (1)If 0<=a<=90 than sin (90-a)=cos a (2)and: sin^α+cos^2 α=1

sin(89)=sin(90-1)=cos(1) ,therefore sin^2 (89)=cos^2 (1) sin(88)=cos(2) 》sin^2(88)=cos^2(2) . . . sin(46)=cos(44) 》 sin^2(46)=cos^2(44) Clearly, there is no need to change further than sin(46).

Substitude back to the question, group it, use(2) than simplify. After the cancelIation, it is not hard to see that only -sin^2 (45)+sin^2 (90) are the only thing left.

-1/2+1=1/2 and we are done.

Pozz Thanapat - 6 years, 1 month ago

Log in to reply

Thanks Pozz for your explanation.

Chew-Seong Cheong - 6 years, 1 month ago

Log in to reply

@Chew-Seong Cheong Thank you very much I got what you've explained me in the post

SHOAIB ur REHMAN - 6 years, 1 month ago

Log in to reply

@Shoaib Ur Rehman I'm glad I can help :)

Pozz Thanapat - 6 years, 1 month ago
Rohan Malik
Jul 31, 2015

As sin^2(A) = cos^2(90-A), and sin^2(A) + cos^2(A) = 1, only sin^2(45) is left

Raymond Lin
Apr 9, 2017

s i n ( x ) = c o s ( 90 x ) sin(x) = cos(90-x) . Therefore, this can be rewritten as s i n 2 ( 1 ° ) + s i n 2 ( 2 ° ) s i n 2 ( 3 ° ) + . . . s i n 2 ( 45 ° ) c o s 2 ( 1 ° ) + c o s 2 ( 2 ° ) c o s 2 ( 3 ° ) + . . . + c o s 2 ( 44 ° ) -sin^2(1°) + sin^2(2°)-sin^2(3°)+...-sin^2(45°) -cos^2(1°)+cos^2(2°)-cos^2(3°)+...+cos^2(44°) Since s i n 2 ( x ) + c o s 2 ( x ) = 1 sin^2(x)+cos^2(x) = 1 , we have 1 + 1 1 + . . . + 1 s i n 2 ( 45 ° ) + s i n 2 ( 90 ° ) = s i n 2 ( 45 ° ) + s i n 2 ( 90 ° ) = ( 2 2 ) 2 + ( 1 ) 2 = 1 2 + 1 = 1 2 -1+1-1+...+1-sin^2(45°) +sin^2(90°) = -sin^2(45°) + sin^2(90°) = -(\frac{\sqrt{2}}{2})^2 + (1)^2 =-\frac{1}{2} + 1 =\frac{1}{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...